CDA: Coordinating data dissemination and aggregation in heterogeneous IoT networks using CTC. (1st December 2020) - Pan, Yan; Li, Shining; Zhang, Yu; Zhu, Ting
Abstract: This paper presents a CDA mechanism to simultaneously coordinate data dissemination and data aggregation services in coexisting heterogeneous IoT networks (i.e., WiFi and ZigBee) using a WiFi Access Point (AP). With CDA, the WiFi signal interference to the low power ZigBee network is mitigated via the latest Cross-Technology Communication (CTC) techniques. The CTC techniques used in CDA are compatible with existing commodity IoT devices, which requires no hardware modification when implementing CDA. Specifically, the individual network status (e.g., duty cycle information) is first exchanged between different networks via CTC. Accordingly, the AP dynamically schedules its channel occupation time based on the communication demand and network status of both networks. Furthermore, a theoretical guidance is provided for the duty cycle control of the ZigBee network in coexisting scenarios, which guarantees the aggregation performance and extends the network's life-time. The proposed CDA mechanism is evaluated through a real-world testbed consisting of 2 WiFi devices and 40 ZigBee nodes. Experimental results show that CDA not only optimizes the ZigBee network's delay and life-time by 3.72 × and 1.24 × , respectively, but also improves the WiFi throughput by 1.94 × .